BIOLOGY OF HILSA ILISHA (HAMILTON) FROM THE CHILKA LAKE WITH AN ACCOUNT ON ITS RACIAL STATUS - Ramakrishnaiah, M (Indian Journal of Fisheries, 2011)
Hilsa ilisha, known locally as 'ilish', forms an important commercial fisheryin the Chilka lake. Chaudhuri (1916) observed the occurrence of the fish in thslake throughout the year, Jones and Sujansingani (1951) tentatively concludedfrom their study of hilsa fishery of the lake that inflow of water from the Dayariver influences the fishery; greater flow of flood water inducing large numberof spawning fish to migrate. They also reported that Chilka hilsa breeds inthe lower reaches of Daya river